PENGEMBANGAN MEDIA FLASHCARD ASSEMBLR BERBANTUAN QR-CODE PADA TOPIK INDONESIAKU KAYA ALAMNYA - Cici Dira Rahmawati; Lina Novita; Resyi A.Gani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Cici Dira Rahmawati. 037121002. Development of Flashcard Assemblr Media assisted by QR-Code on the Topic of My Indonesia is Rich in Nature. This study uses a Research and Development (R&D) approach at Situ Gede 5 Elementary School. The subjects of the study were 30 fifth grade students. This study was conducted in the even semester of 2024/2025. This study began with a needs analysis, curriculum analysis, student analysis and product design. Then develop the flashcard assembly media product, and conductexpert validation, then conduct a trial using the flashcard assembly media assisted by QR-Code on the Topicof My Indonesia is Rich in Nature on predetermined respondents. The results of the study from media experts, language experts, and material experts showed that the flashcard assembly media assisted by QR-Code was very valid and very feasible to use with an average percentage of 98%. In the trial phase, it was carried out with30 students who gave very good and very interesting respondents to use by obtaining an average percentage of 91%. Based on the results of this study, it can be concluded that the flashcard assembly media assisted byQR-Code on the topic of Indonesiaku is rich in nature which was developed in this study is valid, interesting and easy to use by students and is worth learning